Stress tolerance and whole-genome sequencing of an ester-producing Wickerhamomyces anomalus strain - WANG Yujie, WANG Dewei, GONG Tao, LIU Shuangyan, LI Yinfeng, ZHAO Yan, LIU Xiaozhu, ZHANG Xuewen (Zhongguo niangzao, 2025)
In this study, using an ester-producing strain Wickerhamomyces anomalus C11 as the research object, the stress tolerance of the strain was studied by plate growth method. The whole-genome of W. anomalus C11 was sequenced with Illumina second-generation sequencing technology, and the functional genes were annotated and analyzed using clusters of orthologous groups (COG), gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and carbohydrate active enzymes (CAZy) database. The pathogenicity was analyzed based on the pathogen-host interaction (PHI) database. The results demonstrated that W. anomalus C11 exhibited good environmental tolerance to multiple stress conditions, including 100 g/L NaCl, 25 mmol/L H2O2 , 500 mmol/L mannitol, pH 3.0-10.0, low temperature (16 ℃), high temperature (37 ℃), and 40 mmol/L Pb. The W. anomalus C11 genome had a total length of 11.48 Mbp, GC content of 34.42%, and encoded 4 249 genes. The W. anomalus C11 genome was annotated to 1 641, 3 346 and 3 145 functional genes from the COG, GO and KEGG databases, respectively. Additionally, the genome harbored 32 glycoside hydrolase- related genes and 39 glycosyltransferase-related genes, which could contribute to its ester-producing capacity and stress tolerance. Virulence gene prediction identified 676 virulence-attenuated genes, 391 non-virulent genes, 134 avirulent genes, 84 lethal genes, and 39 hypervirulent genes, further confirming W. anomalus C11 had low virulence and high safety.